A importância da história no acto de projectar em Souto de Moura - Indira Joana da Silva Diniz e Nunes (2016)
The theme on debate in this thesis, started with the curiosity to understand the following words said by Souto de Moura: "I believe that the greatest aspiration of an architect is to be anonymous; to be anonymous not out of false modesty but by managing to create, in a given time, a space that will possess the wisdom accumulated over thousands of years; to manage to congregate through his intelligence all that had been done over thousands of years. When nature and artefact coexist in a perfect equilibrium, then what is attained is the supreme stage of art or the silence of things."1 This words gave the idea that exist one past that help the architect to create the one design the present. Therefore, having as object of study the work - written and designed - of Souto de Moura, the question of this work is: what is the importance of history in the act of designing on this architect? This investigation began with the analysis of the written work of Souto de Moura, by reading of interviews and text of this architect, on his words noticed the presence of the names of Aldo Rossi, Robert Venturi and Álvaro Siza Vieira in issues related to the theme of history. In view of this, the work strategy has begun to understand the importance given by Rossi, Venturi and Siza of history in the act of design, through the analysis of his work, written and designed, in a respective chapter, presenting, in parallel, designs of Souto de Moura on it is noticed an association of strategies used in the act of designing. This three chapters are intended to understand the line of thought of each of those architects, for in the final chapter, reverse the discussion and analyze, first, the Souto de Moura work and expose, in parallel, the union point with the ideas of Rossi, Venturi and Siza about the importance of history in the act of designing.